ANALISIS DRPs STATIN DAN ESTIMASI RISIKO ATHEROSCLEROTIC CARDIOVASCULAR DISEASE (ASCVD) PASIEN DIABETES MELITUS TIPE 2 RAWAT JALAN DI RS “X” SAMARINDA - Irham Bakhtiar, Muh.; Novy Yudhistirawati; Hamzah, Hasyrul (JIFI (Jurnal Ilmiah Farmasi Imelda), 2023)
Atherosclerotic Cardiovascular Disease (ASCVD) is the main cause of death in patients with diabetes mellitus with a cardiovascular risk that will increase 2-4 times higher than non-diabetic patients. The statin group is a class of drugs recommended by ACC/AHA 2018 in reducing cardiovascular risk in patients with type 2 diabetes mellitus. This study aims to analyze Drug Related Problems (DRPs) of statin drugs in patients with type 2 diabetes mellitus and calculate the estimated risk for the next 10 years. The research was conducted using a non-experimental descriptive analytic method. Data collection was carried out retrospectively through a population of 194 type 2 diabetes mellitus patients at "X" Samarinda Hospital for the period January-September 2022, 11 patient medical record data were obtained through the Total Sampling technique whose sampling complied with the inclusion and exclusion criteria. The results showed that the most commonly prescribed statins were simvastatin 20 mg in 9 patients (82%), and atorvastatin 20 mg in 2 patients (18%). The results of the DRPs analysis showed that there were 4 cases of DRPs consisting of 1 case of underdose (25%), and 3 cases of drugs not being indicated for the existing medical profile (75%). The total risk level of ASCVD based on the calculation of the ASCVD calculator found that 3 patients (27%) had low risk, 4 patients (36%) medium risk, and 4 patients (36%) high risk.